Emotional Contexts Modulate Anticipatory Late Positive Component and Reward Feedback Negativity in Adolescents With Major Depressive Disorder - Zhang, Wenhai; Liao, Caizhi; Tang, Fanggui; Liu, Shirui; Chen, Jing; Zheng, Lulu; Zhang, Ping; Ding, Qiang; Li, Hong (Frontiers in Psychiatry, 2020)
Background: Neuroimaging research has determined deficits in the dopaminergic circuit of major depressive disorder (MDD) during adolescence. This study investigated how emotional contexts modulate the temporal dynamics of reward anticipation and feedback in adolescents. Methods: EEG data from 35 MDD and 37 healthy adolescents were recorded when they conducted a gambling task after being presented with emotional pictures. Results: The results demonstrated that both MDD and healthy adolescents exhibited the largest late positive component (LPC) in positive contexts at the frontal sites and the largest LPC in negative contexts at the central sites; however, MDD adolescents exhibited anticipatory LPC hypoactivation than healthy adolescents. However, MDD adolescents exhibited smaller gain feedback negativity (FN) than healthy adolescents independent of emotional contexts, positively correlating with the trait anhedonia according to the consummatory aspect of the Temporal Experience of Pleasure Scale. In contrast, MDD adolescents exhibited greater FN loss in positive and neutral contexts than healthy adolescents while no difference in FN loss was found between the two groups in negative contexts. Moreover, the FN loss amplitudes negatively correlated with hedonic tone according to the Snaith-Hamilton Pleasure Scale over the past week. Conclusions: These findings suggest that MDD adolescents exhibited dissociable deficits in reward anticipation and gain or loss feedback that are distinctly modulated by emotional contexts, and they deepen our understanding of the modulation of emotional contexts on the temporal dynamic reorganization of the reward circuit in MDD adolescents.